2021
DOI: 10.1186/s12951-021-01174-y
|View full text |Cite
|
Sign up to set email alerts
|

Insights on functionalized carbon nanotubes for cancer theranostics

Abstract: Despite the exciting breakthroughs in medical technology, cancer still accounts for one of the principle triggers of death and conventional therapeutic modalities often fail to attain an effective cure. Recently, nanobiotechnology has made huge advancement in cancer therapy with gigantic application potential because of their ability in achieving precise and controlled drug release, elevating drug solubility and reducing adverse effects. Carbon nanotubes (CNTs), one of the most promising carbon-related nanomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 188 publications
(173 reference statements)
0
48
0
Order By: Relevance
“…Though the biological barriers and complex TME often impede the penetration of therapeutic agents into deep tumor sites, due to the needle-like nanostructures of CNTs, they can be easily internalized by many cell types, which enhances their tumor penetration in cancer treatment 91 . Besides, the ability of CNTs to absorb light energy in NIR window enables their application in PTT, which facilitates the multifunctional roles of CNTs to serve as both drug vectors and photothermal agents 92 . More interestingly, it was reported that CNTs can transform laser energy into acoustic signals and show great photoluminescence as well as Raman scattering in NIR regions, making them excellent candidates in cancer imaging 93 .…”
Section: Carbon Nanomaterials For Cancer Treatmentmentioning
confidence: 99%
“…Though the biological barriers and complex TME often impede the penetration of therapeutic agents into deep tumor sites, due to the needle-like nanostructures of CNTs, they can be easily internalized by many cell types, which enhances their tumor penetration in cancer treatment 91 . Besides, the ability of CNTs to absorb light energy in NIR window enables their application in PTT, which facilitates the multifunctional roles of CNTs to serve as both drug vectors and photothermal agents 92 . More interestingly, it was reported that CNTs can transform laser energy into acoustic signals and show great photoluminescence as well as Raman scattering in NIR regions, making them excellent candidates in cancer imaging 93 .…”
Section: Carbon Nanomaterials For Cancer Treatmentmentioning
confidence: 99%
“…CNTs containing anti-tumor medicines have poor water solubility, yet this can be improved by surface modification. Proteins and surfactants added to the CNT surface have been proven to not only increase cancer-cell targeting but also minimize toxicity and boost therapeutic effects [116].…”
Section: Surface Modificationmentioning
confidence: 99%
“…Finally, we also note that SWCNT is not the only nanomaterial that has been used to destroy cells. For example, Au nanoshells with a laser power of 4-35 W/cm2 and irradiation for 4 min were used in [32] for it. Many other NIR absorbing nanomaterials with lower laser power.…”
Section: Photothermal Therapy (Ptt) and Photodynamic Therapy (Pdt)mentioning
confidence: 99%